no posible answer
Improved Answer:-
2x2+x-3 = (2x+3(x-1) when factored
Chat with our AI personalities
Let square = [x] -4+3*(-2)*[-4]+[3x-2x]=-4-6-2+[x]=-12+[x]The answer is negative 12 plus squared x.
(2x+3)(2x+4)
(x2-7x+12)/(x2-2x-3)factor the numerator & denominator:(x-4)(x-3)/(x-3)(x-1)now reduce:(x-4)(x-3)/(x+1)(x-3)(x-4)/(x+1)
You have to experiment with different factors of 2, and different factors of 15. In this case, 2x2 - 11x + 15 = (2x - 5) (x - 3)
By factoring I get x-3 divided by x+3